Patients' Experiences of Nurse Case-Managed Osteoporosis Care: A Qualitative Study. (April 2020) - Wozniak, Lisa A; Rowe, Brian H; Ingstrup, Meghan; Johnson, Jeffrey A; McAlister, Finlay A; Bellerose, Debbie; Beaupre, Lauren A; Majumdar, Sumit R
Background: Osteoporosis is a chronic condition that is often left untreated. Nurse case-managers can double rates of appropriate treatment in those with new fractures. However, little is known about patients' experiences of a nurse case-managed approach to osteoporosis care. Objective: Our aim was to describe patients' experiences of nurse case-managed osteoporosis care. Methods: A qualitative, descriptive design was used. We recruited patients enrolled in a randomized controlled trial of a nurse case-management approach. Individual semi-structured interviews were conducted which were transcribed and analyzed using content analysis. Data were managed with ATLAS.ti version 7. Results: We interviewed 15 female case-managed patients. Most (60%) were 60-years or older, 27% had previous fracture, 80% had low bone mineral density tests, and 87% had good osteoporosis knowledge. Three major themes emerged from our analysis: acceptable information to inform decision-making; reasonable and accessible care provided; and appropriate information to meet patient needs. Conclusions: This study provides important insights about older female patients' experiences with nurse case-managed care for osteoporosis. Our findings suggest that this model to osteoporosis clinical care should be sustained and expanded in this setting, if proven effective. In addition, our findings point to the importance of applying patient-centered care across all dimensions of quality to better enhance the patients' experience of their health care.